WINE AS AGRICULTURAL AND FOOD PRODUCT: A HISTORICAL AND COMPARATIVE LEGAL APPROACH - Jovanović, Aleksandra; Atanasovska Cvetkovi, Aneta (Economics of Agriculture, 2022)
Wine is not just a product of modern times. Wine, one of the oldest drinks in the world, was sold and inherited by ancient civilizations. Its importance is indicated by the regulation of wine in the Codes of ancient Mesopotamia and Roman law. Today, this agri-food product is sold on both the domestic and foreign markets, and it is indisputable that the production and sale of this product must be legally regulated. The authors of this paper, by analyzing the legal provisions of Roman law, the Law on Wine and the Criminal Code of Republic of Serbia, point out the importance of the existence and expansion of legal provisions related to wine and its producers and precise criminal law provisions in case of sale of wine produced contrary to legal regulations and contrary to the health of people who consumed the same. The stated purpose of the paper, in order to draw a conclusion about the importance of specifying legal provisions, was achieved by presenting the historical and positive legal regulation, using the historical method and comparative analysis.